2004
DOI: 10.1590/s1516-35982004000800007
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de plantio de gliricídia (Gliricidia sepium (Jacq.) Walp.) em estacas para produção de forragem

Abstract: RESUMO -Gliricídia, uma leguminosa arbórea utilizada no sombreamento de cacaueiros e na produção de forragem, é comumente empregada como cerca viva, madeira e lenha e pode ser multiplicada por sementes e por frações do caule ou de estacas. Conduziu-se este estudo na Escola de Agronomia da UFBA, em Cruz das Almas -Bahia, com o objetivo de avaliar métodos de plantio por estaquia, a fim de se identificar aquele de maior índice de pegamento das estacas, maior produção de forragem e menor custo de implantação. O de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Gliricidia can be easily grown from seeds; however, it can also be easily established by stakes COSTA et al (2004), in order to evaluate planting methods by cuttings, using different stem fractions to identify those of forage production, observed that 1m cutting vertically planted in pits had the highest leaf dry matter production, and the mean production was 1.29Mg ha -1 of total leaf dry matter, with density equivalent to 40,000 plants ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Gliricidia can be easily grown from seeds; however, it can also be easily established by stakes COSTA et al (2004), in order to evaluate planting methods by cuttings, using different stem fractions to identify those of forage production, observed that 1m cutting vertically planted in pits had the highest leaf dry matter production, and the mean production was 1.29Mg ha -1 of total leaf dry matter, with density equivalent to 40,000 plants ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…De fácil estabelecimento, propaga-se por sementes, mudas ou por estaquia (Drumond et al, 1990;Carvalho Filho et al, 1997;Costa et al, 2004). Essa forrageira é conhecida nos países de língua espanhola como madre do cacau, madero negro e mata ratón.…”
Section: Introductionunclassified
“…Leguminosa nativa no México, América Central e Norte da América do Sul, sendo de crescimento rápido e enraizamento profundos. De fácil estabelecimento, propaga-se por sementes, mudas ou por estaquia (Drumond et al, 1990;Carvalho Filho et al, 1997;Costa et al, 2004). Essa forrageira é conhecida nos países de língua espanhola como madre do cacau, madero negro e mata ratón.…”
Section: Introductionunclassified